האלמנטים המשותפים בשיריהם של משה בן עזרא ואבו פיראס אלחמדני (מחקר השוואתי) Elements common in the poems of Musa son of Izra and Abu Firas al-Hamdani (A comparative study) (Journal of the College of Languages (JCL), 2018)
Abstract: Musa son of Yaqoob son of Izra, the Spanish poet, linguist, and philosopher, was born in Granada. He has many poems representing types of poetry. Also, he had important books, such as "the Poetry of Israel" and "Contemplative Research". He is knowledgeable in both Hebrew and Arabic, because most of his books were written in Arabic and the then translated to Hebrew. It seemed that he was influenced by Arab poets, specifically Abo Firas, and borrowed many issues, such as comparison, repetition, exaggeration, etc. and included them in his poetry. All know that Arabic literature clearly influenced Hebrew literature in the Spanish era. Arabic literature is rich in quantity, and from which Hebrew poets took form it. Son of Izra was keen in tackling such matters and scrutinized things carefully, and exploited this ability in understanding Hebrew literature and sacred books.